Upaya Menemukan Kesimbangan Hubungan Pusat Dan Daerah - sudi fahmi (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Itis obvious, that the Decentralization that occurred through Law No. 22/1999 granted the political decentralization. However, the substance of Law No. 32/2004 is administrativedecentralization. It is suspected that through Law No.23/2004 re-centralization in local governance has occurred.